2017
DOI: 10.23917/biomedika.v8i2.2910
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Ibu Tentang Imunisasi Dasar Dengan Kelengkapan Imunisasi Dasar Bayi Di Wilayah Kerja Puskesmas Bendo Kabupaten Magetan

Abstract: Imunisasi merupakan suatu strategi yang efektif dan efisien dalam meningkatkan derajat kesehatan nasional. Alasan bayi tidak mendapatkan imunisasi lengkap karena faktor informasi, mengakibatkan pengetahuan ibu tentang imunisasi kurang. Tujuan dari penelitian ini adalah untuk mengetahui hubungan pengetahuan ibu dengan kelengkapan imunisasi dasar bayi di wilayah kerja Puskesmas Bendo Kabupaten Magetan. Desain penelitian adalah penelitian observasional analitik dengan pendekatan cross sectional. Sampel penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
1
4
1
7
Order By: Relevance
“…The results of this study are not in line with the results of research conducted by Sari (2015) who said that most mothers in the working area of Bendo Health Center in Magetan Regency have good knowledge of basic immunization as many as 34 people (52.3%).…”
Section: Mother's Knowledge Of Basic Immunization In Infants Aged 0-9 Months In the Work Area Of The South Alalak Health Center In Banjarcontrasting
confidence: 99%
“…The results of this study are not in line with the results of research conducted by Sari (2015) who said that most mothers in the working area of Bendo Health Center in Magetan Regency have good knowledge of basic immunization as many as 34 people (52.3%).…”
Section: Mother's Knowledge Of Basic Immunization In Infants Aged 0-9 Months In the Work Area Of The South Alalak Health Center In Banjarcontrasting
confidence: 99%
“…20 This study could strengthen a research at health centre of Bendo, in Magetan concluding that parents who had proper education and knowledge about immunization tended to have completely basic immunization for their children compared to parents who had less education and knowledge. 21 However, according to a research conducted by Septariani et al, levels of education did not affect attitudes of parents, especially mothers in immunizing their children. Based on the study conducted in Sukarapih village, Sukasari subdistrict, it was found that counselling affected mothers' knowledge.…”
Section: Discussionmentioning
confidence: 91%
“…It is supported by the results of study by Suhaid & Faranita, (2018), which stated that there was a relationship between knowledge with full immunization status of infant in Alamendah village, Rancabali, Bandung. Furthermore, the results of the study Sari, et. al., (2016) added that there was also a significant relationship between mothers' knowledge about basic immunization with full immunization of infants in the work area of Bendo Health Center, Magetan.…”
Section: Resultsmentioning
confidence: 98%